The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3402/ejpt.v7.31509
|View full text |Cite
|
Sign up to set email alerts
|

PTSD and depression construct: prevalence and predictors of co-occurrence in a South Lebanese civilian sample

Abstract: BackgroundArmed conflict, occupation, and political and economic instability that are particularly experienced by the civilian Lebanese population of South Lebanon would almost inevitably affect these individuals psychologically. Therefore, identifying predictors of co-occurring mental disorders is paramount to sound assessment and intervention planning.ObjectiveThis study aims to determine the prevalence and predictors of co-occurring posttraumatic stress disorder (PTSD) and major depressive disorder (MDD) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 52 publications
4
24
1
1
Order By: Relevance
“…A 2016 study has shown a PTSD prevalence of 23.4% in a survey of a southern Lebanese civilian sample. 20 The striking difference in PTSD prevalence between studies within the same year can be attributed to the cluster munition injury that the participants of our study endured.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…A 2016 study has shown a PTSD prevalence of 23.4% in a survey of a southern Lebanese civilian sample. 20 The striking difference in PTSD prevalence between studies within the same year can be attributed to the cluster munition injury that the participants of our study endured.…”
Section: Discussionmentioning
confidence: 73%
“…Other studies have also shown that unemployment and low functionality are associated with lower mental health conditions, namely PTSD. 20 56 We believe that the economic costs of PTSD are attributable to lost work productivity; the severity of the injury and the associated functional impairment definitely play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Adding to the pre‐existing refugee communities, mostly from Palestine and Iraq, Lebanon now accounts for the country with the highest number of refugees per capita . The most recent lifetime prevalence estimate of PTSD amongst Syrian refugees living in camps in Lebanon is estimated at 35.4% , substantially higher than the recent general population estimate of 8.8% .…”
Section: Introductionmentioning
confidence: 71%
“…The protective role of social support against PTSD has been highlighted extensively (Bryant 2016;Farhood and Dimassi 2012;Farhood and Noureddine 2003;Farhood et al 2013;Olff 2017). The Lebanese culture fortunately treasures and values social support (Farhood et al 2016). Socio-culturally sensitive micro-policies should be executed such that social support that is available to families is enhanced.…”
Section: Gender Differences In Risk Factors Associated With Ptsdmentioning
confidence: 99%